Insecticide resistant Anopheles from Ethiopia but not Burkina Faso show a microbiota composition shift upon insecticide exposure - Netsanet Worku; Antoine Sanou; Juliane Hartke; Marion Morris; Fatoumata Cissé; Salimata Ouédraogo; Madou Tapsoba; Nicola Vallon; Tewodros Debebe Akilu; Ligabaw Worku; Moussa Wamdaogo Guelbeogo; Victoria A. Ingham (Parasites & Vectors)
Abstract Background Malaria remains a key contributor to mortality and morbidity across Africa, with the highest burden in children under 5. Insecticide-based vector control tools, which target the adult Anopheles mosquitoes, are the most efficacious tool in disease prevention. Due to the widespread use of these interventions, insecticide resistance to the most used classes of insecticides is now pervasive across Africa. Understanding the underlying mechanisms contributing to this phenotype is necessary to both track the spread of resistance and to design new tools to overcome it. Methods Here, we compare the microbiota composition of insecticide-resistant populations of Anopheles gambiae, An. coluzzii and An. arabiensis from Burkina Faso, and in the latter case additionally from Ethiopia, to insecticide-susceptible populations. Results We show that the microbiota composition between insecticide-resistant and -susceptible populations does not differ in Burkina Faso. This result is supported by data from laboratory colonies originating in Burkina Faso across two countries. In contrast, An. arabiensis from Ethiopia demonstrates clear differences in microbiota composition in those dying from and those surviving insecticide exposure. To further understand resistance in this An. arabiensis population, we performed RNAseq and saw differential expression of detoxification genes associated with insecticide resistance and changes in respiration, metabolism and synapse-related ion channels. Conclusions Our results indicate that, in addition to changes in the transcriptome, microbiota can contribute to insecticide resistance in certain settings. Graphical Abstract